1997
DOI: 10.1177/014556139707601109
|View full text |Cite
|
Sign up to set email alerts
|

p53 Immunostaining of Surgical Margins as a Predictor of Local Recurrence in Squamous Cell Carcinoma of the Oral Cavity and Oropharynx

Abstract: Local and regional recurrence is the principal reason for treatment failure in squamous cell carcinoma (SCC) of the head and neck. The conventional method of evaluating surgical margins for cellular atypia does not always predict risk of local recurrence accurately. Immunostaining of surgical margins for tumor markers may provide a more precise evaluation of risk of local recurrence. Paraffin-embedded tissue blocks of surgical margins from 24 patients with oral cavity and oropharyngeal squamous cell carcinoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 16 publications
1
35
0
3
Order By: Relevance
“…Hence, much attention has recently been focused on the evaluation of molecular pathologic prognostic factors. Previously, immunohistochemical studies have revealed that positive staining for markers of genomic alteration in histologically negative surgical margins are correlated with a high recurrence rate of cancers (Ball et al 1997;Smith et al 2000;Zhang et al 2008). To our knowledge, correlations between Survivin and CD44v6 expression in surgical margin and prognosis of laryngeal cancer have not been reported up to date.…”
Section: Introductionmentioning
confidence: 93%
“…Hence, much attention has recently been focused on the evaluation of molecular pathologic prognostic factors. Previously, immunohistochemical studies have revealed that positive staining for markers of genomic alteration in histologically negative surgical margins are correlated with a high recurrence rate of cancers (Ball et al 1997;Smith et al 2000;Zhang et al 2008). To our knowledge, correlations between Survivin and CD44v6 expression in surgical margin and prognosis of laryngeal cancer have not been reported up to date.…”
Section: Introductionmentioning
confidence: 93%
“…Several studies demonstrate that p53 expression correlates with tumor grade and recurrence (23). Alterations in the p63 gene have been proposed as one of the factors responsible for tumorigenesis in oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Mutation analysis of the P53 gene using a PCRsingle strand conformation polymorphism method in breast cancers has been shown to provide useful prognostic information [49]. Ball et al [50] and Cruz et al [51] demonstrated p53 immunoexpression in non-malignant oral mucosa of the resection margins and concluded that it may be a valuable predictor for local recurrences. In addition p53 gene mutations have been implicated as markers of tumour spread in synchronous oral cancers.…”
Section: P53 and Microsatellitesmentioning
confidence: 99%